The Prevalence of musculoskeletal impairment in traffic police of District Swabi, Pakistan.: Musculoskeletal impairment in traffic police of District Swabi - Ahmad, Zahoor; Anwar, Kinza; Naz, Umaira; Tariq, Khizra; Noor, Mah; Anwar, Junaid (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
The number of vehicles has been increasing out of proportion for the capacity of road infrastructure in particular in developing countries. The duty of a traffic police officer includes the implementation of daily traffic regulations. This involves long-standing hours and also particular repeated body movements. There is limited literature available on the musculoskeletal disorders develop among traffic police. Therefore this study was designed to include 219 traffic police officers from 23 traffic booths of district Swabi, Pakistan. Data was collected using a structured questionnaire and Cornell Musculoskeletal Discomfort Questionnaires (CMDQ). Informed consent was taken before filling the questionnaire. Age distribution of the participants was grouped as: 20 to 30 years (n=51, 23.4%), 31 to 40 years (n=141, 64.7 %), and over 40 years (n=26, 11.9%). Out of 219, 23% were diabetics, hypertensive participants were 21.9% (n=48), while 54% (n=120) had no history of chronic illness. The majority of traffic cops in district Swabi reported mild discomfort in their shoulders, arms, forearms, thighs, lower legs, knees, and feet, but moderate discomfort in their neck and back. The results of the study indicate that the traffic cops in the district of Swabi suffer back and neck pain, causing them to have moderate difficulty doing their duties.